2023
DOI: 10.1101/2023.04.12.23288455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Lasting Legacy of COVID-19: Exploring the Long-Term Effects of Infection, Disease Severity, and Vaccination on Health and Cognitive Function

Abstract: COVID-19 affects a variety of organs and systems of the body including the central nervous system. Recent research has shown that COVID-19 survivors often experience neurological and psychological complications that can last for months after infection. We conducted a large internet study using online tests to analyze the effects of SARS-CoV-2 infection, COVID-19 severity, and vaccination on health, intelligence, memory, and information processing precision and speed in a cohort of 4,446 subjects. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 51 publications
2
1
1
Order By: Relevance
“…The minimal or absent impact of merely contracting the infection on physical and mental health and cognitive performance, which contrasts with results of many already published studies, e.g. (Altuna, Sánchez-Saudinós, Lleó, & 2021; Delgado-Alonso et al, 2022; Flegr & Latifi, 2023; Havervall et al, 2021; Lamontagne et al, 2021; Lu et al, 2020; Marchi et al, 2023; Mazza et al, 2020; O’Mahoney et al, 2023; Zhao et al, 2020) could be related to the fact that all students included in our study were younger than 31 years old (95% were 20-24 years old). As is often the case with such a young population, most students experienced a relatively mild form of COVID-19; only about 20% described it as “severe flu,” and none of the study participants was hospitalized due to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The minimal or absent impact of merely contracting the infection on physical and mental health and cognitive performance, which contrasts with results of many already published studies, e.g. (Altuna, Sánchez-Saudinós, Lleó, & 2021; Delgado-Alonso et al, 2022; Flegr & Latifi, 2023; Havervall et al, 2021; Lamontagne et al, 2021; Lu et al, 2020; Marchi et al, 2023; Mazza et al, 2020; O’Mahoney et al, 2023; Zhao et al, 2020) could be related to the fact that all students included in our study were younger than 31 years old (95% were 20-24 years old). As is often the case with such a young population, most students experienced a relatively mild form of COVID-19; only about 20% described it as “severe flu,” and none of the study participants was hospitalized due to COVID-19.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results align with previous studies that have identified a correlation between COVID-19 severity and subsequent declines in physical health (Flegr & Latifi, 2023; Han, Zheng, Daines, & Sheikh, 2022; Iqbal et al, 2021; Mizrahi et al, 2023), mental health challenges (Putri, Arisa, Hananto, Hariyanto, & Kurniawan, 2021; Shanbehzadeh, Tavahomi, Zanjari, Ebrahimi-Takamjani, & Amiri-Arimi, 2021; Zeng et al, 2023), and cognitive deficits (Ariza et al, 2023; Guo et al, 2022; Miskowiak et al, 2021). Collectively, these findings suggest that individuals with a history of more severe COVID-19 symptoms typically face more pronounced post-infection complications.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations